Radiocarbon dating, carbon and nitrogen content, sediment accumulation rate and palaeomagnetic data of the EV13 sediment core from coastal lake Eilandvlei, southern Cape coast, South Africa - Michael Wündsch; Torsten Haberzettl; Michael E Meadows; Kelly L Kirsten; Thomas Kasper; Jussi Baade; Gerhard Daut; Joseph S Stoner; Roland Mäusbacher (PANGAEA, 2016)
A 30.5 m sediment core was recovered from the coastal lake Eilandvlei (EV13), which represents a unique high-resolution record of environmental change for southern Africa. For the establishment of a robust chronology, special emphasis was placed on the calibration of radiocarbon (14C) ages obtained from the dating of different material. However, the reliability of 14C ages can be problematic since coastal lakes interact with different source pools providing 14C-depleted ("old") carbon thus causing reservoir effects. The origin of old carbon affecting the EV13 samples was most likely sourced from the Indian Ocean. Two pre-bomb marine molluscan shells were therefore analysed to determine the regional marine reservoir offset (dR), with obtained dR values of 134 ± 38 and 161 ± 38 14C yrs providing the first available data for the south coast of South Africa. However, the application of the resulting average dRmean = 148 ± 27 14C yrs for the calibration of the entire EV13 record underestimates the variable reservoir effects throughout the Holocene. These were possibly caused by past changes in the connectivity between the present lake system and the ocean as well as a varying degree of upwelling in this area. To solve this problem, three sample pairs (each consisting of wood fragments and bulk organic sediment from the same core depth) were dated to calculate the variable past reservoir effects. This approach provided a median basal age of 8920 +200/-250 cal BP. Palaeomagnetic secular variation stratigraphy was used to corroborate the chronology for the topmost 1.5 m of the record (past millennium), thus providing the first Holocene sediment based inclination and declination data from South Africa.
Supplement to: Wündsch, M et al. (2016): The impact of changing reservoir effects on the 14C chronology of a Holocene sediment record from South Africa. Quaternary Geochronology, 36, 148-160, https://doi.org/10.1016/j.quageo.2016.08.011